The Influence of the Traditional Game Prepet Jengkol on Increasing Student Motivation in Physical Education Learning - Mulya, Gumilar (Bravo's : Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2023)
Traditional games are games that are passed down from generation to generation. Apart from training dexterity and balance, traditional games also have ancestral values that need to be preserved. This research aims to see the influence of the traditional game prepet jengkol on students' motivation in learning physical education. This research uses a quantitative research approach with the research design used is a pretest-posttest control group design. The population in this study were all class VIII students at SMPN 5 Tasikmalaya City. The samples were taken from two classes using class randomization and obtained from an experimental class of 32 students and a control class of 33 students. The instrument used is a learning motivation instrument which consists of 30 statements to be answered by students. Data analysis was carried out descriptively and inferentially using SPPS 28. The results of the data analysis showed that there was an influence of the traditional game prepet jengkol on increasing student motivation in learning physical education. These results show that the traditional game prepet jengkol can be an alternative in physical education learning.